Religious revival and secularism in post-Soviet Azerbaijan - Wiktor-Mach, Dobrosława (Religion and society, 2017)
The book explores the complex world of Islam from the perspective of its adherents and activists in Azerbaijan. Baku, the most secular Muslim capital city, is a battlefield for the minds and souls of "ethnic Muslims." Visiting pirs was till now the typical expression of religiosity among Azerbaijani Muslims. Sunni-Shia division was blurred. Nowadays, Shia and Sunni Muslim movements propose new distinctive